Simulation of Cement Mill to Predict and Mitigate the Over-Heat Phenomenon: an Approach to Optimize the Energy Consumption in Cement Industry - Petrus, Himawan Tri Bayu Murti; Kristanto, Jonas; Wanta, Kevin Cleary; Prasetya, Agus (International Series on Interdisciplinary Science and Technology, 2019)
being one of the most energy-intensive industries, cement industry requires to evaluate the energy efficiency of their operating units, one of them is cement mill. Functioning as a mixing unit of several materials, i.e., clinker, limestone, gypsum, and trass with their initial heat and propensity of heat generation during milling, over-heat in the cement mill occurs frequently. It should be avoided in order to establish efficiency. Therefore, a mathematical model was generated in this study to predict and to mitigate this overheat phenomenon. This cement mill mathematical model has been generated using mass and energy balances. The output of the model is temperature profile versus residence time with targeted water content of the product that the optimum residence time can be calculated. Based on the temperature profile with a targeted water content of the product, it can be concluded that the optimum operating condition of the cement mill lies in the range of 5 to 30 seconds of materials residence time in the cement mill